A Comparative Study of Electronic-Based Sexual Violence: Maqashid Shari'ah Perspective on Indonesia's Law No. 12 of 2022 and Malaysia's Legal Framework (Program Studi Hukum Keluarga Islam, 2025)
In order to combat the growing problem of sexual assault, particularly that which occurs through digital media, the Sexual Violence Criminal Acts Law (Law No. 12 of 2022) was introduced. It is crucial to determine if this law complies with the goals of Islamic law, or Maqashid Shari’ah, given that the majority of Indonesia’s population is Muslim. The types of Electronic-Based Sexual Violence that are covered by the law and their assessment from the standpoint of Maqashid Shari'ah are the two main topics of this study. Using a normative legal research approach with literature analysis, this study finds that the law identifies three forms of electronic-based sexual violence: (1) recording or taking sexual images without consent, (2) transmitting sexual content against the recipient's will, and (3) online sexual harassment or stalking. These actions contradict Maqashid Shari’ah as they cause harm and are explicitly prohibited in Islam. While the law seeks to provide protection and aligns with the broader goals of Maqashid Shari’ah, its implementation of Islamic values remains gradual (tadarruj) rather than comprehensive. This research contributes both theoretically and practically by offering insights into legal and Islamic perspectives on electronic-based sexual violence.